Phase transformation and microstructure study of the as-cast Cu-rich Cu-Al-Mn ternary alloys - Holjevac-Grgurić T.; Manasijević D.; Kožuh S.; Ivanić I.; Balanović Lj.; Anžel I.; Kosec B.; Bizjak M.; Knežević M.; Gojić M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Four Cu-rich alloys from the ternary Cu-Al-Mn system were prepared in the electric-arc furnace and casted in cylindrical moulds with dimensions: f=8 mm and length 12 mm. Microstructural investigations of the prepared samples were performed by using optical microscopy (OM) and scanning electron microscopy, equipped by energy dispersive spectroscopy (SEM-EDS). Assignation of crystalline phases was confirmed by XRD analysis. Phase transition temperatures were determined using simultaneous thermal analyzer STA DSC/TG. Phase equilibria calculation of the ternary Cu-Al-Mn system was performed using optimized thermodynamic parameters from literature. Microstructure and phase transitions of the prepared as-cast alloys were investigated and experimental results were compared with the results of thermodynamic calculations.